Modeling of the Solar Thermal Energy Use in Urban Areas - Qerimi, Drita; Dimitrieska, Cvete; Vasilevska, Sanja; Rrecaj, Arlinda Alimehaj (Salehan Institute of Higher Education, 2020)
Most of the generated electricity in Kosovo is produced from fossil fuel, a part of the energy comes from the import, while participation of renewable resources is symbolic, and a bias between the grid extension and the load of power generated sometimes results in shortage of electricity and thus frequent power cuts. The use of renewable energy and particularly the solar thermal energy represents one of the most promising alternative strategies. In Kosovo, the global horizontal radiation ranges from 1241 kWh/m2 per year in Shterpce to 1461 kWh/m2 per year in Gjakova, while the average for Kosovo can be estimated at 1351 kWh/m2 per year. The average sun duration for the city of Pristine is 5.44 h, while the average horizontal irradiation is 3.79 kWh/mÂ² per day. Participation of energy consumption in household is still dominant - about 41.4% of the total consumption in Kosovo, 15% of this energy is used for domestic hot water. This energy demand can be lowered significantly by using improved building construction techniques and utilization of RES-s, especially solar thermal. The first step is to map the city in different areas to locate suitable locations for the installation of solar collectors serving sanitary hot water. The demand for sanitary hot water varies from object to object, this variation depends on whether the building is individual or collective, school institutions or religious buildings, for this reason the classification of buildings was done according to the request for sanitary hot water. After that the demand for sanitary hot water is calculated for several different institutions: Residential houses, Dormitories and Hospitals. For all of the above-mentioned cases the data for: solar fraction, solar contribution, CO2 avoided, collector temperature, financial analysis etc. are gained using the TSOL 2018 software. To evaluate the active energy for a time period, the daily, monthly and annual performance for three systems which are located in University Clinical Center of Pristine, Kosovo have been analyzed. In addition the results of the mathematical model, simulation and measured solar energy contribution for solar station in Infective disease clinic have been compared. In this paper, a proposal for replacing the conventional water heaters with the domestic solar water heaters (DSWH) is made. A case study for 38289 Residential households in Pristine has been selected. The initial cost of the solar water heater for the city is 60113730 â‚¬. The system saves 7274910 â‚¬ annually and reduced Cð‘‚2 emission by 22973400 kg. The results from the paper show that the DSWH is economically feasible in Pristine and can result in fuel saving and CO2 emission reduction.